A CASE STUDY ON THE TECHNICAL FEASIBILITY OF FABRICATING A 700-BAR PRESSURE VESSEL USING THE DESIGN-BY-ANALYSIS (DBA) APPROACH AT PT PLN (PERSERO) - Yanurarzaqa Ghiffari; Zulfikar Manggau; Muhamad Habibi (Bulletin of Engineering Science, Technology and Industry, 2026)
Green-hydrogen deployment requires storage vessels capable of sustaining very high pressure while maintaining structural integrity and manufacturability. This study evaluates the technical feasibility of manufacturing a Type II hydrogen pressure vessel at PT PLN (Persero) PUSHARLIS using a Design-by-Analysis approach supported by finite element analysis. The study integrates engineering standards, material screening, workshop observations, design calculations, ANSYS simulation, manufacturing review, and hydrostatic-test planning. The proposed vessel uses an AISI 4130 steel liner with a 49 mm wall and a 14 mm composite hoop-wrapping layer under a 70 MPa (700 bar) internal pressure. Simulation produced a maximum von Mises stress of 381.75 MPa, below the 1,186 MPa yield strength adopted for the liner, with a minimum safety factor of approximately 3.05. The hydrostatic-test scheme uses 910 barg, equivalent to 1.3 times the design pressure. Local ASTM A36 can support prototype manufacturing-process development, but its lower strength makes it unsuitable for long-term high-pressure hydrogen storage. The results indicate a feasible domestic manufacturing pathway provided that high-pressure code qualification, material compatibility, testing capability, and quality assurance are strengthened.